Lexical cohesion and tone in Nigerian newspaper editorials - Malah, Zubairu (2016)
Drawing on the notion of Systemic Functional Linguistics (SFL), researchers have variously explored texts of different registers and genres in attempts to account for the varying features of texts responsive to different conditions of their production in authentic social interactions (see, for example, Li, 2010; Ansary and Babaii, 2009; Taboada, 2004; Martin, 2001; Hasan, 1984). Among the fields of research in this tradition is cohesion analysis, which is concerned with discourse relations that transcend grammatical structure (Halliday, 1994; Halliday and Hasan, 1976). Similarly, this study drew on SFL and focused on Lexical Cohesion and Tone in Nigerian newspaper editorials. The objectives of the study were the following: to identify the types of lexical cohesion used in the editorials, to examine how lexical cohesion is utilized in building coherence in the editorials, and to examine how the lexical devices are used to signal the writers’ tones. The research approach was qualitative. The data, which was culled online from websites of 4 major Nigerian newspapers: The Guardian, The Nation, Leadership, and Vanguard, comprised editorial texts written on social issues only. The editorials were sampled for a period of 6 months: May to October, 2015. This gave a total of 40 editorial texts and 24,456 words. For the analysis of lexical cohesion, the study applied Eggins’ (2004) lexical cohesion framework; and for examining writers’ tones, the study utilized a constructed framework based on adaptation of Flemming (2012), Flemming (2011), Kolins (2009), and Kane (2000). The analyses revealed 3,186 lexical ties intersententially, and that the major sources of lexical cohesion in newspaper editorials were repetition (49%), expectancy relations (15.78%), synonymy (11.29%), and class/sub-class relations (11.11%). It was also observed that lexical cohesion, in forms of long chains, short chains, and simple ties were used in building coherence in the editorial texts. On relation between lexical ties and tones of writers, the data suggested that 1,170 (36.7%) ties contributed in signalling the writers’ tones.